2006
DOI: 10.1001/jama.296.20.2460
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Nosocomial Infection in Cardiac Surgery by Decontamination of the Nasopharynx and Oropharynx With Chlorhexidine Gluconate

Abstract: clinicaltrials.gov Identifier: NCT00272675.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
215
0
13

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(233 citation statements)
references
References 34 publications
5
215
0
13
Order By: Relevance
“…The median time to onset of S. aureus SSI after surgery was 19 days (IQR, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], whereas the time to onset of S. aureus BSI was 18 days (IQR, 10-44).…”
Section: Overall Study Populationmentioning
confidence: 99%
“…The median time to onset of S. aureus SSI after surgery was 19 days (IQR, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], whereas the time to onset of S. aureus BSI was 18 days (IQR, 10-44).…”
Section: Overall Study Populationmentioning
confidence: 99%
“…Chlorhexidine at varying concentrations, however, has been evaluated in more than 11 trials. Impacts on VAP rates have been variable: three reported decreases [64][65][66] while the other eight did not [67][68][69][70][71][72][73][74]. One trial reported a decrease in antibiotic usage for patients treated with chlorhexidine [67].…”
Section: Oral Antiseptics and Antibioticsmentioning
confidence: 99%
“…Impacts on other outcomes, however, have been more uniformly disappointing. One trial did report a decrease in mortality [67] and one reported a decrease in duration of hospitalization [66], but these findings were not borne out by the other nine studies. A meta-ana lysis including the six trials published through 2007 suggested a net 44% decrease in VAP rates but no decreases in patients' ventilator days, hospital days or mortality [75].…”
Section: Oral Antiseptics and Antibioticsmentioning
confidence: 99%
“…[10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]33 Nasal mupirocin is considered the best topical agent for the eradication of gram-positive bacteria immediately following the treatment, when the adherence to this protocol is high. 35 As shown in chart 1, 68.8% of the studies that used topical mupirocin for patient decolonization achieved an effective outcome.…”
Section: Discussionmentioning
confidence: 99%
“…5,37 Nevertheless, studies indicated that when used as an agent for the decolonization of MRSA, despite interrupting its transmission, 10 the effectiveness of chlorhexidine is improved when used with other drugs, such as mupirocin. 26,42 Among the analyzed studies, 90.9% of those that tested chlorhexidine obtained effective outcomes for decolonization, 10,12,[15][16]19,22,24,26,29,31 observing that 72.7% of them used chlorhexidine in combination with other drugs. 12,[15][16]19,22,24,26,31 Octenidine dihydrochloride and povidoneiodine are topical antimicrobial agents, both used for skin cleansing and antisepsis for the purpose of preventing infections.…”
Section: Discussionmentioning
confidence: 99%